Decomposition and sequential-AND analysis of known cyber-attacks on critical infrastructure control systems. Issue 1 (15th December 2020) - Maynard, Peter; McLaughlin, Kieran; Sezer, Sakir
Abstract: We perform a detailed survey and analysis of the most significant attacks, which have targeted industrial control systems over the past decade, based on detailed incident reports from scientific and non-traditional resources. This work is the first that considers together a comprehensive set of real-world cyber-attacks with the purpose of deriving a set of common features focusing particularly on the process control network. Each attack is decomposed to provide a comprehensive overview followed by a discussion of the commonalities identified across attacks. To achieve this, each attack is modelled using Attack Trees with Sequential AND, and mapped to the industrial control system Cyber Kill Chain. We focus on the methods of intrusion rather than the identification of actors. This article can be read in two parts: first, an analysis of each attack, and secondly a discussion of the derived commonalities. The resulting commonalities can be used to develop improved detection strategies to detect modern adversarial techniques and tactics.